The Principles of Justice in International Law - MAMEDOV, Andrey A.; GREBENNIKOV, Valeriy V.; ALEKSEEVА, Diana G.; LAVRENTEVA, Marya S.; VINOGRADOVA, Stanislava A. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
Background/Objectives . The article is devoted to the principles of law governing the organization of judicial proceedings in international law. There are a number of principles of justice, such as the rule of law, the independence of judges, the reasonable period of proceedings, counterclaim, publicity, and others. This article covers not all, but some of them, which, in the authors' opinion, are the most publicly significant in the administration of justice. The most widely considered is the well-known principle of legality, which includes several aspects, including the prohibition of retroactive application of the law and the prohibition of the analogy of law. This article also emphasizes the importance of making a list of principles of justice. Methods . The main method of research is comparative analysis. Other scientific methods were also used in the study, such as: interdisciplinary synthesis, logical method, analogy method, specification, classification, and systematization. Conclusions . Among the general principles of law, there are some special provisions relating to justice. Such principles are applied in judicial proceedings at both the national and international levels of justice. A complete list of such principles has not yet been made. This study emphasizes the need to define and classify the principles of justice. In the context of the general nature of this study, it is understood that some of the issues raised in the article may be the subject of further research. In the absence of legal norms, the results of the study of the principles of justice applicable in international law could be very useful, especially for judges.